Public Opinion about Surface Water and Groundwater Quality in Florida - Tatiana Borisova; John Brett; Cassel Gardner (EDIS)
FE844, a 6-page illustrated report by Tatiana Borisova, John Brett, and Cassel Gardner, summarizes the results of a public survey about the quality of surface water and groundwater resources in Florida. Published by the UF Department of Food and Resource Economics, October 2010.